New species and new records of mites of the family Laelapidae (Acari: Mesostigmata) associated with ants in Iran - Joharchi, Omid; Halliday, Bruce; Saboori, Alireza; Kamali, Karim (Zootaxa, 2011)
This paper reports on four species of mites of the family Laelapidae associated with ants in Iran—Gymnolaelaps messor sp. nov. from Messor sp., Gymnolaelaps prestoni sp. nov. from Myrmica sp., Myrmozercon karajensis sp. nov. from Camponotus sp., and Pseudoparasitus missouriensis (Ewing, 1909) from Camponotus sp. This is the first record of Myrmozercon from Iran. The genera Gymnolaelaps and Pseudoparasitus are distinguished from each other and from the related genus Laelaspis by the shape, ornamentation and chaetotaxy of the genital shield, the form of the palp tarsal claw, and the presence or absence of pre-sternal plates.